1994
DOI: 10.1007/bf01224775
|View full text |Cite
|
Sign up to set email alerts
|

The value of the Lugol's iodine staining technique for the identification of vaginal epithelial cells

Abstract: This paper reports on the specificity of the Lugol's iodine staining technique for the detection of vaginal epithelial cells on penile swabs. Air-dried swabs taken from the glans of the penis of 153 hospital patients and from 50 healthy volunteers, whose last sexual intercourse had taken place at least 5 days previously, were stained with Lugol's solution. Glycogenated cells were found in more than 50% of the cases studied, even in healthy volunteers without urethritis. In almost all of these cases the smear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 3 publications
0
15
0
3
Order By: Relevance
“…19 22) Lugol's staining technique has long been used as a speciˆc test for vaginal squamous cells, 21,22) but is no longer considered su‹ciently speciˆc since glycogen-containing cells exist in male oral and urethral squamous cells. 23,24) In addition, most laboratories do not have speciˆc antibody reserves.…”
Section: Introductionmentioning
confidence: 99%
“…19 22) Lugol's staining technique has long been used as a speciˆc test for vaginal squamous cells, 21,22) but is no longer considered su‹ciently speciˆc since glycogen-containing cells exist in male oral and urethral squamous cells. 23,24) In addition, most laboratories do not have speciˆc antibody reserves.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of various mucins and glycogen in epithelial cells is well known [1,[6][7][8][10][11][12][13][14][15][16]. Mucins belong to a family of mucopolysaccharides that protect the epithelial cell lining of the vagina and are either present on the cell surface of superficial epithelium or secreted [11].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most promising techniques, first reported in the 1970s, was Lugol's iodine that identified vaginal cells by the presence of glycogen granules [6][7][8]. However, the absolute specificity of this technique has since been questioned, with several studies demonstrating the presence of glycogenated squamous cells also in oral mucosa, the male urinary tract and on the glans penis [6][7][8]. The approach is therefore now deemed unsuitable for use in forensic laboratories.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Systematic investigations have shown that the Lugol's staining method can no longer be used as proof of the presence of vaginal cells on penile swabs from a suspected sexual offender, as glycogen-containing squamous epithelial cells can also be found in the male urethral mucosa [9][10][11]. A reliable method for the specific morphological identification of vaginal epithelial cells is not yet available.…”
Section: Introductionmentioning
confidence: 97%